PS-BPC02-3: EVALUATION OF VASCULAR FUNCTION FOR PREDICTION OF RENAL PROGNOSIS IN JAPANESE PATIENTS WITH LIFESTYLE-RELATED DISEASES. (January 2023) - Masuda, Shiho; Hara, Tomoyo; Yamagami, Hiroki; Mitsui, Yukari; Kurahashi, Kiyoe; Yoshida, Sumiko; Otoda, Toshiki; Yuasa, Tomoyuki; Nakamura, Shingen; Kuroda, Akio; Endo, Itsuro; Matsuhisa, Munehide; et al.
Abstract : Background: Since chronic kidney disease (CKD) is associated with the development of serious cardiovascular diseases such as stroke, coronary artery disease and heart failure, prevention and early diagnosis of CKD are important clinical issues. Many risk factors including diabetes, hypertension, dyslipidemia, obesity, and cigarette smoking are known to be involved in the development of CKD; however, there is no available biomarker that can predict the progression of CKD at an early stage. Although it has been reported that glomerular endothelial injury causes development of CKD, it remains unclear whether evaluation of vascular endothelial function can predict renal prognosis. Therefore, in the present study, we examined the association between vascular endothelial function and longitudinal eGFR change in patients with lifestyle-related diseases. Methods: We retrospectively evaluated 341 Japanese patients (176 males and 165 females; mean age, 63.87 ± 12.02 years) with lifestyle-related diseases in whom baseline vascular function was evaluated by flow-mediated dilation (FMD) and brachial-ankle pulse wave velocity (baPWV) and in whom 24-month longitudinal eGFR values were recorded after vascular testing at Tokushima University Hospital and Anan Medical Center, Tokushima Japan. The association between values of FMD and eGFR slope and the association between values of baPWV and eGFR slope were statistically analyzed. Statistical significance was set at p < 0.05. Results: Single regression analysis showed that value of FMD was positively associated with eGFR slope in females (p < 0.001) and non-smoking males (p = 0.033) but not in smoking males (p = 0.133). Multiple regression analysis including confounding factors demonstrated that the value of FMD remained a contributor against annual eGFR decline in females (p = 0.002) and non-smoking males (p = 0.046) but not in smoking males (p = 0.266). On the other hand, the value of baPWV had no significant association with eGFR slope regardless of sex and smoking. Conclusions: In patients with lifestyle-related diseases, FMD value can be used for prediction of renal prognosis represented by the eGFR slope in females and non-smoking males. Thus, early comprehensive intervention for improving vascular endothelial function might lead to a better renal prognosis in female and non-smoking male patients with lifestyle-related diseases.